PASIEN PROLANIS HIPERTENSI TIDAK TERKONTROL DI WILAYAH KERJA PUSKESMAS KEBUN HANDIL TAHUN 2022 - Fauziah, Nadila; Jammin, Maria Inge; Darmawan, Armaidi (Scientific Of Environmental Health and Diseases, 2023)
ABSTRACTBackground: Hypertension is one of the top 10 causes of death and remains a major challenge inIndonesia. The World Health Organization (WHO) estimates that currently the prevalence ofhypertension globally is 22% of the total world population. Of these patients, only less than a fifth makeefforts to control their blood pressure. At Kebun Handil Community Health Center, based on data takenfrom P-Care from January to May 2023, it was found that the average number of hypertensive patientsregistered as Prolanis members was 1180 patients but of these, only 1.81% were under control fromthe target of 5% or an average of only 22 people under control.Method: This final project is based on data found at the health center. After the data collection processis complete, the data is processed using SPSS and analyzed using the problem solving cycle method.The cycle starts from problem identification by brainstorming, after collecting several problems thatexist in the low coverage of controlled hypertension in prolanis patients at the Kebun Handil HealthCenter, then the problem is confirmed with primary or secondary data.Conclusion: The low coverage of controlled hypertension in prolanis patients at the Kebun HandilCommunity Health Center is due to the low compliance of hypertension prolanis patients in taking theirmedication so that problem solving is carried out in the form of creating an attractive and innovativeposyandu.Keywords: Hypertension, ProlanisAB